Outcome of Progressive Multifocal Leukoencephalopathy Treated by Interleukin‐7. Issue 4 (18th February 2022) - Lajaunie, Rébecca; Mainardi, Ilaria; Gasnault, Jacques; Rousseau, Vanessa; Tarantino, Andrea G.; Sommet, Agnès; Cinque, Paola; Martin‐Blondel, Guillaume; ,
Abstract : Objective: Restoring anti‐JC virus (JCV) immunity is the only treatment of progressive multifocal leukoencephalopathy (PML). Interleukin‐7 is a cytokine that increases number and function of T cells. We analyzed a population of PML patients who received recombinant human IL‐7 (rhIL‐7) to estimate survival and its determinants. Methods: After exclusion of patients with missing data or receiving other immunotherapies, findings from 64 patients with proven PML who received rhIL‐7 between 2007 and 2020 were retrospectively analyzed. Logistic regression was used to analyze variables associated with one‐year survival. Results: Underlying conditions were HIV/AIDS (n = 27, 42%), hematological malignancies (n = 16, 25%), primary immunodeficiencies (n = 13, 20%), solid organ transplantation (n = 4, 6%) and chronic inflammatory diseases (n = 4, 6%). One‐year survival was 54.7% and did not differ by underlying condition. Survival was not associated with baseline characteristics, but with a >50% increase in blood lymphocytes (OR 4.1, 95%CI 1.2–14.9) and CD4 + T cells (OR 5.9, 95%CI 1.7–23.3), and a > 1 log copies/mL decrease in cerebrospinal fluid JCV DNA (OR 7.6, 95%CI 1.6–56.1) during the first month after rhIL‐7 initiation. Side effects were mainly local and flu‐like symptoms (n = 8, 12.5%) and PML‐immune reconstitution inflammatory syndrome (IRIS) (n = 5, 8%). Interpretation: In this non‐controlled retrospective study, survival did not differ from that expected in HIV/AIDS patients, but might have been improved in those with hematological malignancies, primary immunodeficiencies and transplant recipients. RhIL‐7 might have contributed to the increase in blood lymphocytes and decrease in CSF JCV replication that were associated with better survival. ANN NEUROL 2022;91:496–505